2016
DOI: 10.1177/0018720816655941
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Imperfect Conflict Resolution Advisory Aids for Future Air Traffic Control

Abstract: CRA aid offers benefits across traffic densities, regardless of its imperfection, as long as its reliability level is set above the threshold of assistance, suggesting its application for future ATC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 39 publications
(66 reference statements)
0
21
0
Order By: Relevance
“…Loft et al (2016) found their participants took as long as 20 s to accept queries, taking longer when SA was low or uncertainty was high. Trapsilawati, Wickens, Qu, and Chen (2016) reported means latencies in accepting a SPAM probe of between 9 and 23 s. Strybel, Vu, Battiste, and Johnson (2013) reported that 5% of probes went unanswered, and Cunningham et al (2015) found that pilots did not respond the ready prompt 16% of the time in their study due to workload. Further two additional studies showed that SPAM latency measures are correlated with NASA TLX scores, indicating that it is associated with workload (Strybel et al, 2010; Strybel et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Loft et al (2016) found their participants took as long as 20 s to accept queries, taking longer when SA was low or uncertainty was high. Trapsilawati, Wickens, Qu, and Chen (2016) reported means latencies in accepting a SPAM probe of between 9 and 23 s. Strybel, Vu, Battiste, and Johnson (2013) reported that 5% of probes went unanswered, and Cunningham et al (2015) found that pilots did not respond the ready prompt 16% of the time in their study due to workload. Further two additional studies showed that SPAM latency measures are correlated with NASA TLX scores, indicating that it is associated with workload (Strybel et al, 2010; Strybel et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Second, the results could be used as the inputs for the development of conflict resolution aid (CRA), a tool that not only alerts ATCOs about an impending conflict but also provides an advisory to resolve the conflict (Trapsilawati et al, 2016). Converging and crossing conflicts were proven to be most cognitively demanding for human operators; hence, the algorithm for resolution advisory generation of these conflicts should be carefully designed and must consider ATCO cognitive resources.…”
Section: Discussionmentioning
confidence: 99%
“…The philosophy of our CAT tool was on the contrary to let the controller decide which maneuvers to implement. Trapsilawati et al (2016) showed higher performance, lower workload and no decrease in situation awareness with the CRA tool. However, the present study illustrated that for conflicts involving more than two aircraft, at least two maneuvers were usually required.…”
Section: Sitmentioning
confidence: 94%
“…Other ATC decision aids have been evaluated with the more direct objective to be implemented in operational settings. For instance, Trapsilawati et al (2016) assessed a conflict detection and resolution advisory tool, the CRA. This tool shows predicted conflicting pairs of aircraft, the resolution maneuver advisory is explicitly written (e.g., "aircraft A climb FL140") and the controller can accept or reject the proposed resolution.…”
Section: Sitmentioning
confidence: 99%